2021
DOI: 10.1007/s40684-021-00367-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards Green 3D-Microfabrication of Bio-MEMS Devices Using ADEX Dry Film Photoresists

Abstract: Current trends in miniaturized diagnostics indicate an increasing demand for large quantities of mobile devices for health monitoring and point-of-care diagnostics. This comes along with a need for rapid but preferably also green microfabrication. Dry film photoresists (DFPs) promise low-cost and greener microfabrication and can partly or fully replace conventional silicon-technologies being associated with high-energy demands and the intense use of toxic and climate-active chemicals. Due to their mechanical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 56 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…This correlation function is obtained using a so-called Hanbury Brown and Twiss interferometer. It is observed that, at zero delay time, g (2) (0) is smaller than 1 but bigger than 0.5, measured from a polymer dot fabricated at 8 mW in the formulation containing QDs diluted by 5 times. This indicates that only few QDs (more than 1 but less than 5) are trapped inside this given polymer dot.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This correlation function is obtained using a so-called Hanbury Brown and Twiss interferometer. It is observed that, at zero delay time, g (2) (0) is smaller than 1 but bigger than 0.5, measured from a polymer dot fabricated at 8 mW in the formulation containing QDs diluted by 5 times. This indicates that only few QDs (more than 1 but less than 5) are trapped inside this given polymer dot.…”
Section: Resultsmentioning
confidence: 90%
“…This indicates that only few QDs (more than 1 but less than 5) are trapped inside this given polymer dot. 92,93 We then decreased the QD concentration to 0.05 mg QDs/1 g (PETA/MES) and obtained a correlation function at zero delay of g (2) (0) ∼ 0.3 < 0.5, which is the signature of a single-photon source, thus corresponding to a single QD trapped in this specific polymer dot (Figure 7g).…”
Section: Resultsmentioning
confidence: 99%
“…Using the adjusted fields, this method enables the formation of acoustic streaming-induced drag force to complement, rather than compete or dominate, the acoustic radiation force and act as an assisting mechanism to efficiently collect submicron particles, down to 200 nm particles, and form two highly focused particle streams inside a 150-μm-wide and 50-μm-high channel at the wavelength of 300 μm as shown in Figure . While a popular approach in MEMS, circuit board fabrication, and, only recently, for passive microfluidics, to the best of our knowledge, no report of using laminated DFR for particle manipulation purposes in SAW-driven technologies has been proposed. The defined and reproducible manufacture of SAW acoustofluidic chips on the wafer scale using this technique obviates the fundamental limits of soft-lithography including bonding inconsistencies, alignment issues, and microchannel deformation.…”
Section: Introductionmentioning
confidence: 99%
“…ADEX and SUEX are dry film photoresists based on the same chemistry as liquid SU-8 resists and are available at thicknesses ranging from 5 µm to over 500 µm [ 2 , 3 ]. While the cost per wafer is higher than with liquid resists, the capital costs to perform dry film lamination are far lower and the failure rate due to defects is substantially improved [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%